Echocardiography in Pediatric Pulmonary Hypertension - Jone, Pei-Ni; Ivy, D. Dunbar (Frontiers in Pediatrics, 2014)
Pulmonary hypertension (PH) can be a rapidly progressive and fatal disease. Although right heart catheterization remains the gold standard in evaluation of PH, echocardiography remains an important tool in screening, diagnosing, evaluating, and following these patients. In this article, we will review the important echocardiographic parameters of the right heart in evaluating its anatomy, hemodynamic assessment, systolic, and diastolic function in children with PH.